Knowledge management and economic intelligence in Japan - Violeta Mihaela Dincă (The International Journal of Management Science and Information Technology (IJMSIT), 2013)
Knowledge management holds a broad range of meanings. Within this article I tried to reveal Japan's position regarding this discipline. I emphasized how knowledge is being managed on a daily basis at the state level, business, or even at individual level. Also the article emphasizes the important role of economic intelligence for an efficient knowledge management. It addresses how to evaluate the methods used by the Japanese, and exceed the usual speculation and classical assertions regarding the superiority of Japanese intelligence, what is the part of the organization or of the cultural aspect within these practices and finally if these Japanese methods are exported.
Keywords: 650; knowledge management; Japanese companies; economic intelligence